Overview Smart Hotel di Indonesia yang Merupakan Trend Baru dalam Industri Perhotelan - Adiati, Maria Pia (Bina Nusantara University, 2011)
Nowadays we can find out many taglines featuring the word Smart Hotel or Smart Traveler. Smart traveler is those who travel in a smart way. We called it smart because they choose the accomodation and the transportation wisely, in accordance with requirements and budget. Meanwhile Smart Hotel tagline comes up since there are many smart travelers who travel a lot to the cities around the world. Smart Hotels are hotels who try to accommodate the current market demands. The latest trend for the travelers is only a clean and comfort accommodation with affordable price but covers all the basic things needed for the travelers. Nowadays, travelers pass most of the time out of the hotel for doing business or either for visiting tourism objects. Typical smart hotels are hotels with 2 stars or 3 stars rating. Even though it is 2 or 3 star hotel, the service is as good as the higher ratings.Some of the hotel management or hotel group try to suite the demand by releasing 2 star or 3 star brand. And in the future, the 2 star or 3 star hotel is the hotel who will rapidly grow and take the majority market since the price is affordable and suites the budget.